دور سمعة بلد المنشأ في اتخاذ القرارات الشرائية دراسة ميدانية على مستخدمي السيارات السياحية الخاصة في الساحل السوري (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يتناول البحث أثر سمعة بلد المنشأ على اتخاذ القرار الشرائي في الأسواق الدولية, حيث إنّ سمعة بلد المنشأ أصبحت أحد الموضوعات الأكثر أهميةً في مجال الأعمال والتجارة الدولية, وقد تم تناول الجوانب الآتية في البحث: - سلوك المستهلك واتخاذ القرارات الشرائية . - سمعة بلد المنشأ . - دور سمعة بلد المنشأ في اتخاذ القرار الشرائي . ومن ثم تم التعرف على مدى اهتمام المستهلك في الساحل السوري بمعرفة بلد المنشأ للسيارة, وأثر ذلك على قراره الشرائي، وذلك من خلال الدراسة الميدانية التي أجريت وتحليل البيانات التي تم الحصول عليها, وكان من أهم نتائج البحث: أ- يتم الاعتماد على سمعة بلد المنشأ عند الاختيار واتخاذ قرار الشراء باعتبار أن هذه السمعة تعد مؤشراً لجودة السيارة، خاصة بالمقارنة مع البدائل المتاحة من السيارات والتفضيل بينها . The research dials with the effect of the Country-of-Origin Reputation on making purchase decisions in the international market, since the reputation or the country-of-origin has become one of the most important issues in the field of the international trade and business. The research discusses the following sides: - Consumer Behavior and the Purchase Decision-Making. - Country-of-Origin Reputation. - The Role of the Country-of-Origin Reputation on Purchase Decision-Maki. It has been also found out the extent to which the Syrian Coast consumer is interested in knowing the Country-of-Origin of the car, and its effect on his purchase decision through the empirical survey done, and the analysis of the acquired data. One of the most significant findings of the research is: Consumers depend on the Country-of-Origin reputation in choice and make purchase decision for this reputation as an indicator of the high quality of the car, particularly compared with the available offers of cars and the distinction between them.